2021
DOI: 10.1097/md.0000000000026593
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and genotype distribution of human papilloma virus in cervical squamous intraepithelial lesion and squamous cell carcinoma in Taizhou, China

Abstract: Human papillomavirus (HPV) infection is a common sexually transmitted disease worldwide and the leading cause of cervical cancer. Current vaccines do not cover all HPV genotypes whereas the distribution of HPV genotypes varies in different geographic regions. The study aimed to investigate the distribution of HPV genotypes in patients with cervical squamous intraepithelial lesion (SIL) and cervical squamous cell carcinoma (SCC) in Taizhou City of Jiangsu Province, China. A total of 940 patients including 489 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Age is one of the most important factors in uencing HPV infection, and in the present study, HPV infection in high-grade squamous intraepithelial lesions (CIN II and III) was noted in patients aged 40-49 years. This nding was similar to that in studies from Taizhou and Jiangsu provinces [14,32]. The age group with the highest prevalence of HPV in the ICC group was the ≥ 60 years group(incidence: 46.17%); this incidence was higher than that in the 50-59 years age group in a study from Taizhou [14], higher than that in the 40-44 years age group in a study from Shanghai and Zhejiang [33], and higher than that in the 41-50 years age group in a study from Jiangsu [32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Age is one of the most important factors in uencing HPV infection, and in the present study, HPV infection in high-grade squamous intraepithelial lesions (CIN II and III) was noted in patients aged 40-49 years. This nding was similar to that in studies from Taizhou and Jiangsu provinces [14,32]. The age group with the highest prevalence of HPV in the ICC group was the ≥ 60 years group(incidence: 46.17%); this incidence was higher than that in the 50-59 years age group in a study from Taizhou [14], higher than that in the 40-44 years age group in a study from Shanghai and Zhejiang [33], and higher than that in the 41-50 years age group in a study from Jiangsu [32].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, HPV 52, 16, and 58 were found to be the major contributors to CIN I and II, and HPV 16, 58, and 52 were the major contributors to CIN III and ICC, Similar to Shanxi Province [20], Distinguish from Jiangsu and Sichuan [14,23]. On the whole, these ndings are similar to those of previous domestic and international studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[4][5][6] Prevalence of HPV infection and type-specific distribution vary greatly between nations 7 and between grades of cervical cytology. [8][9][10][11][12][13] Data on the prevalence and distribution of HPV types by cervical cytology grade from regions in Europe characterized by high cervical cancer incidence and mortality are scarce. 6,7,14 Various types of medical data (electronic health records, billing data, registries) are generated at a high speed and the growth in research involving data mining (DM) and artificial intelligence (AI) in health care has been exponential.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have documented significant regional differences in hrHPV prevalence worldwide (including in women with normal cytology and invasive cancer) . Prevalence of HPV infection and type-specific distribution vary greatly between nations and between grades of cervical cytology . Data on the prevalence and distribution of HPV types by cervical cytology grade from regions in Europe characterized by high cervical cancer incidence and mortality are scarce …”
Section: Introductionmentioning
confidence: 99%